Kinetics of the neutrophil‐lymphocyte ratio during PD‐1 inhibition as a prognostic factor in advanced hepatocellular carcinoma. (24th May 2021) - Choi, Won‐Mook; Kim, Ji Yoon; Choi, Jonggi; Lee, Danbi; Shim, Ju Hyun; Lim, Young‐Suk; Lee, Han Chu; Yoo, Changhoon; Ryu, Min‐Hee; Ryoo, Baek‐Yeol; Kim, Kang Mo
Abstract: Background and Aims: Programmed death 1 (PD‐1) inhibitors have improved survival outcomes and produced durable responses in advanced hepatocellular carcinoma (HCC) for some patients. Here, we evaluated the relationship between the baseline and kinetics of the neutrophil‐lymphocyte ratio (NLR) and clinical outcomes in nivolumab‐treated HCC patients. Methods: All consecutive HCC patients treated with nivolumab between July 2017 and June 2020 were screened for the eligibility. The NLRs were calculated before and at 2, 4 and 6 weeks after treatment. Survival outcomes were compared based on the baseline and kinetics of NLR. We additionally analysed the association of the baseline and dynamic changes in the NLR with hyperprogression (HPD). Results: Among the 194 included cases, most patients were male (82.0%) and had a Child–Pugh Class A disease (70.6%). Patients with a baseline NLR ≥ 3 (hazard ratio [HR] 2.46; 95% CI 1.63‐3.71) had a poorer overall survival than patients with baseline NLR < 3. During the treatment, the NLR increased rapidly in patients developing HPD, and only a ΔNLR at 4 weeks was predictive of HPD. The risk of HPD increased by 20% for every 20% increase in the ΔNLR at 4 weeks. Accordingly, an NLR increase at 4 weeks (HR 1.79; 95% CI 1.19‐2.68) was associated with an increased risk of death, especially among patients with a baseline NLR ≥ 3. Conclusions: The baseline and on‐treatment kinetics for the NLR are effective prognostic indicators in nivolumab‐treated patients with HCC. This may help to guide patient selection and on‐treatment strategies for immunotherapies in advanced HCC.